Calcified ovarian fibromas complicated with basal cell nevus syndrome - Daiken Osaku; Fuminori Taniguchi; Hiroaki Komatsu; Hermawan Wibisono; Yukihiro Azuma; Tasuku Harada (Wolters Kluwer Medknow Publications, 2021)
Basal cell nevus syndrome (BCNS) is a rare neurocutaneous syndrome characterized by tumorigeneses such as basal cell carcinomas, jaw cysts, ovarian fibromas, and cardiac fibromas. We present a 24-year-old female with calcified ovarian fibromas associated with BCNS. She had a surgical history of the maxillary cyst and was diagnosed with BCNS due to the cutaneous pits. Magnetic resonance imaging indicated an 8-cm mass and a 4-cm mass, which had been suspected to be a subserosal myoma and a fibroma, respectively. GnRH agonist was preoperatively administered; however, the size of the masses did not change. In laparoscopy, a tumor consisting of 8- and 5-cm masses in the right ovary was identified, and tumorectomy was performed. Because both tumors were extraordinarily rigid and could not be morcellated with scalpels or scissors, we removed them by the Luer Bone Rongeurs with minilaparotomy. The histopathological diagnosis was the ovarian fibromas with marked calcification.